2004
DOI: 10.1021/jf049845a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Ripening Degree on the Oxidative Stability and Organoleptic Properties of Cv. Nostrana di Brisighella Extra Virgin Olive Oil

Abstract: The evaluation of the influence of olive ripening degree on the stability of extra virgin olive oils by the determination of the oxidative stability index, the DPPH(*) radical test, and the quali-quantitative analysis of phenolic compounds, as well as the study of the variation of their sensory profiles, plays a key role in the assessment of the overall olive oil quality. Olives of the cv. Nostrana di Brisighella grown in the north-central Italian region of Emilia-Romagna were picked at four different stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
172
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(209 citation statements)
references
References 18 publications
32
172
1
4
Order By: Relevance
“…Oils were shown to move from extra virgin olive oil to VOO when the olives were beyond the optimum stage of ripeness. This agrees with the results published by Rotondi et al (2004) [12]. In contrast, Gimeno et al (2002) [13] reported that the stage of ripeness was not associated with significant differences in the quality parameters of olive oil including the FFA content.…”
Section: Effect Of Ripenesssupporting
confidence: 91%
See 1 more Smart Citation
“…Oils were shown to move from extra virgin olive oil to VOO when the olives were beyond the optimum stage of ripeness. This agrees with the results published by Rotondi et al (2004) [12]. In contrast, Gimeno et al (2002) [13] reported that the stage of ripeness was not associated with significant differences in the quality parameters of olive oil including the FFA content.…”
Section: Effect Of Ripenesssupporting
confidence: 91%
“…During ripening, important chemical changes occur inside the drupe [4] and may affect the quality of the olive oil [10] [11]. In this study, we have found that the free acidity, the rate of polyunsaturated fatty acid synthesis and the sensory evaluation are affected by the ripeness of the pressed olives.…”
Section: Effect Of Ripenessmentioning
confidence: 75%
“…On the other hand, a significant decrease of total phenols content during ripening was previously reported (Skevin et al, 2003;Rotondi et al, 2004;Baccouri B. et al, 2007). This decrease was most likely correlated with the increased activity of hydrolytic enzymes observed during ripening (Amiot et al, 1989).…”
Section: Discussionmentioning
confidence: 60%
“…In order to attenuate such these taste sensations, the authors suggested the need to postpone harvesting of Coratina olives. A Quantitative Descriptive sensory Analysis (QDA) carried out by Rotondi et al [130] confirmed a decreasing trend of the positive olive oil descriptors, such as bitterness and pungency, when Nostrana di Brisighella olives ripened. The highest statistically significant intensity was at the beginning of fruit skin pigmentation.…”
Section: Sensory Properties Elicited By Phenols In Voomentioning
confidence: 94%